(untitled) (BIRDEM Medical Journal, 2012)
Objectives: This study was performed to find out the extent and nature of arterial flow abnormality in diabetic patients with peripheral neuropathy compared to diabetic patients without neuropathy, using duplex colour Doppler technique. Materials and method: This cross sectional study was performed on diabetic subjects in the Department of Radiology and Imaging, BIRDEM from July 2008 to May 2009. Patients were referred from Department of neurology and preventive foot care OPD, BIRDEM, for colour Doppler imaging of lower limb arteries. Total 88 consecutive diabetic patients were included in this study. Out of them 48 were diagnosed cases of diabetic neuropathy (group I) and 40 were diabetic without neuropathy (Group II). In all patients the Ankle Brachial Index (ABI) and Pulsatility Index (PI) were recorded on both left and right lower limb arteries, by using duplex colour Doppler technique. Total no. of patients were 88. 48 had neuropathy. They were 27-57 yrs of age. Result: Unpairedt test was used to find out relationship between the variables.P value <o.o5 was considered as statistically significant. The mean ABI was 1.44±0.07, ranged from 1.30 to 1.59 in group I (diabetic neuropathy) and 1.17±0.06, ranged from 1.05 to 1.26 in group II (diabetic without neuropathy). The mean ABI difference was found statistically significant (p<0.05) between group I and group II. The mean PI was 3.0±0.69, ranged from 1.18 to 3.68 and 7.97±2.29,ranged from 5.50 to 13.0 in group I (diabetic neuropathy) and group II (diabetic without neuropathy) respectively. The mean PI difference was found statistically significant (p<0.05) between group I (diabetic neuropathy) and group II (diabetic without neuropathy). Conclusion: In this study it was observed that Pulsatility Index (PI) decreased and Ankle Brachial Index (ABI) increased in diabetic neuropathic group. There was significant difference of Pulsatility Index (PI) and Ankle Brachial Index (ABI) found between diabetic subjects with and without neuropathy. So, from the finding of the present work, it can be said that diabetic neuropathy affect the arterial flow detected by non invasive duplex colour Doppler imaging may help in proper patient management and may prevent neuropathic arterial complications. But for any definine conclusion, bigger appropriate study should be done. DOI: http://dx.doi.org/10.3329/birdem.v2i2.12309 (Birdem Med J 2012; 2(2): 89-92)